Analysis of the Impact of Household Waste on the Environment and Drinking Water Sources of Pontang Subdistrict Residents and its Implications for Biology Learning - Alivia Chesa Nadinda Putri; Enggar Utari (International Journal of STEM Education for Sustainability, 2025)
Population growth harms water resources in terms of both quality and quantity. The negative impact in quantity is the occurrence of environmental pollution, such as water, soil, and air pollution. The negative impact in quality is a decrease in the quality of natural resources, especially pollution of water resources in the surrounding environment, so that a decrease in the quality of clean water available to the community results in an increase in disease rates, damages aquatic ecosystems and affects economic activity in the environment. Waste disposal and management are two factors that affect environmental quality. Household garbage or waste is waste from daily activities, such as used water from bathing, washing, or cooking waste. Waste disposal and management, especially household wastes, are still poorly handled. All of these things have a huge impact on environmental pollution in Pontang Subdistrict, especially on the drinking water source for the residents of Pontang Subdistrict. This research was conducted qualitatively using survey, observation, and interview methods. The results showed that the impact of household waste in Pontang Subdistrict pollutes the environment by reducing the aesthetics of the environment, causing unpleasant odors and becoming seeds of disease material. The impact of household waste on drinking water sources in Pontang Subdistrict causes drinking water sources consumed to have a color that is not clear, smells, and tastes so that there may be microorganisms that cause various sources of digestive diseases. Implications for biology learning utilizing group discussions, field trips or project-based. The application of impact is useful for students and the community in raising awareness about the importance of environmental awareness.